Innovations in groundwater recharge - International Water Management Institute (International Water Management Institute, 2002)
Based on research presented in the technical paper ?Artificial recharging of groundwater: An experiment in the Madhya Ganga Canal Project, India, by R. Sakthivadivel and A. S. Chawala